The Integrated Six-Sigma Method to Reduce Losses in the Production and Supply Chain Process (Case Study: Polyethylene Pipe and Fittings Company) - Zainab Hadi Mahdi; Abbas Hadi Abbood (International Journal of Supply Chain Management, 2018)
Abstract- In recent years, the use of six sigma techniques has been expanded. In today's competitive world, six sigma can be a winning company to improve quality and reduce costs. The purpose of this study was to investigate the Six Sigma approach to reducing losses in the production and supply chain process at Polyethylene Pipe and Fittings Company. The statistical population of this study was 1100 employees of the company. A sample of 285 people was selected using the Morgan table as a sample. The data collection tool was a researcher-made questionnaire. The reliability of the questionnaire was confirmed by experts and the reliability of the questionnaire was confirmed by Cronbach's alpha coefficient and for data analysis, Pearson correlation coefficient was used. The results of this study showed that six sigma dimensions include leadership and vision, management commitment and resources, customer focus, right people selection, improvement management and process, company strategy have a positive and significant relationship with reducing waste in the products and supply chain process. Keywords- Six sigma, Waste products, Polyethylene, Company, Production and Supply Chain Process.